Atomic and Specificity Details of Mucin 1 O-Glycosylation Process by Multiple Polypeptide GalNAc-Transferase Isoforms Unveiled by NMR and Molecular Modeling - Coelho, Helena (2022)
IF/00780/2015 PTDC/BIA-MIB/31028/2017 UIDP/04378/2020 UIDB/04378/2020 LA/P/0140/2020 SFRH/BD/140394/2018 PD/BD/142847/2018 PD00065/2013 DL 57/2016 ROTEIRO/0031/2013-PINFRA/22161/2016 BFU2016-75633-P PID2019-105451GB-I00 E34_R17 LMP58_18 to R.H-G RTI2018-099592-B-C21 ITN, GA-642157 COST Action GLYCONanoProbes (CA18132) ERC-2017-AdG, project number 788143-RECGLYCANMR RTI218-094751-B-C21) DNRF107